Pengaruh Media Pembelajaran Bagan Pohon Dan Papan Pintar Cuaca Terhadap Hasil Belajar Siswa Pada Tema 5 Subtema 2 Di Kelas III SD Negeri 173292 Butar T.A 2022/2023 - Ladi Ladita Sigalingging; Wildansyah Lubis (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The problem in this study is the low learning outcomes of class III students at SD Negeri 173292 Butar T.A 2022/2023. This study aims to determine the effect of student learning outcomes with the use of learning media Tree Charts and Smart Boards on Theme 5 Sub-theme 2 Weather Changes. Class III SD Negeri 1733292 Butar Academic Year 2022/2023. Location The research was conducted at SD Negeri 1733292 Butar. The sample of this study were all students of class III SD Negeri 1733292 Butar, which consisted of 2 classes, namely: Class IIIA (Experimental Class 1) and Class IIIB (Experimental Class 2). Class III A with a total of 20 students and class IIIB with a total of 20 students. The sample collection technique with Total Sampling is the selection of a sample where the entire population is selected as a sample. This type of research is a quasi-experimental research design with Non Equivalent Multiple Group Design and quantitative data. The data collection tool used to determine student learning outcomes is an objective test with a total of 25 questions that have been tested for validation and reliability. From the data analysis with a sample of 20 students in experimental class 1 and 20 students in experimental class 2, it was obtained that the average of experimental class 1 was at Pre-Test 41 and Post-Test 82 while in experimental class 2 at Pre-Test 41.4 and Post- Tests 78.4. At a significant level ꭤ=0.05. Both classes are normally distributed because Lo<Lt is 0.116<0.190 (experimental class 1) and 0.176 (experimental class 2). Homogeneity test in the Post-Test experimental class 1 and experimental class 2 with Fcount<Ftable, namely 1.68<2.17. The t-test was carried out at the significant level ꭤ=0.05 that tcount>ttable is 1.874>1.685. The writer concludes that there is a significant effect of Tree Chart and Smartboard learning media on Theme 5 Sub-theme 2 Weather Change. Class III SD Negeri 1733292 Butar Academic Year 2022/2023